2011
DOI: 10.2147/ijn.s17711
|View full text |Cite
|
Sign up to set email alerts
|

Solid self-nanoemulsifying cyclosporin A pellets prepared by fluid-bed coating: preparation, characterization and in vitro redispersibility

Abstract: Background: The objective of this study was to evaluate fluid-bed coating as a new technique to prepare a pellet-based solid self-nanoemulsifying drug delivery system (SNEDDS) using cyclosporin A as a model of a poorly water-soluble drug. Methods: The rationale of this technique was to entrap a Liquid SNEDDS in the matrix of the coating material, polyvinylpyrrolidone K30, by fluid-bed coating. Pseudoternary phase diagrams were used to screen the liquid SNEDDS formulatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(6 citation statements)
references
References 28 publications
(32 reference statements)
0
6
0
Order By: Relevance
“…Samples were gold-coated by Q150R sputter coater (Quorum Technologies Ltd, East Sussex, UK). The process was carried out in an argon atmosphere, at 20 mA for 1 min and involved applying 3–10 KV excitation electron energy [ 30 ]. Sieve analysis study was performed for pellet size distribution.…”
Section: Methodsmentioning
confidence: 99%
“…Samples were gold-coated by Q150R sputter coater (Quorum Technologies Ltd, East Sussex, UK). The process was carried out in an argon atmosphere, at 20 mA for 1 min and involved applying 3–10 KV excitation electron energy [ 30 ]. Sieve analysis study was performed for pellet size distribution.…”
Section: Methodsmentioning
confidence: 99%
“…Diffraction patterns of pure TPGS, F127, and CyA were used as references for the evaluation of various micellar nanoformulations. Reference spectra indicated that CyA existed in a crystalline state before incorporation into the micellar formulations (Figure ia); the diffractogram of raw CyA powder showed characteristic high-intensity diffraction peaks at 2θ values of 6.86° (011), 7.8° (102), 9.26° (110), 10.76° (112), 12.58° (022), 14.48° (201), 15.04° (202), 15.2° (210), 16.78° (124), 18.6° (131), 19.38° (132), 20.84° (027), 22.14° (230), 23.28° (042), and 24.28° (119). , Pure F127 also showed two characteristic peaks with the highest intensity at 2θ angles 19.13 and 23.32°, indicating that F127 is a crystalline adjuvant . The characteristic peaks 18.12 and 22.32° of TPGS were observed in the diffraction pattern of TPGS .…”
Section: Resultsmentioning
confidence: 99%
“…042), and 24.28°(119). 30,31 Pure F127 also showed two characteristic peaks with the highest intensity at 2θ angles 19.13 and 23.32°, indicating that F127 is a crystalline adjuvant. 32 The characteristic peaks 18.12 and 22.32°of TPGS were observed in the diffraction pattern of TPGS.…”
Section: Elementalmentioning
confidence: 98%
“…Kolliphor ® P 407 showed two peaks at 19.346 • and 23.472 • angles (2 θ) [16]. Polyvinylpyrrolidone-K30 did not show these typical diffraction peaks due to its amorphous nature [39], indicating a broad and diffused pattern as its molecules are randomly arranged in a crystal lattice [40]. Furthermore, the PXRD of formulation KP407 (TD 3 ) with 1:4:3 ratio (drug: binary polymer:ternary polymer) revealed only one small peak, reflecting a high conversion of crystalline drug into amorphous form.…”
Section: Pxrd Studiesmentioning
confidence: 97%